Youtubeurs et webséries : un temps pour commenter - Jean Châteauvert (Communiquer)
This temporalist analysis explores comments left on the margins of webseries and vlogs through their temporal dimensions (time of publication, content and dynamics) and the games of temporality they introduce into the viewing experience. The purposes of these comments vary over the exchanges: open the exchanges, react to the publication or video, comment a personal experience or squatte these exchanges to divert users to new platforms. During the exchanges, the comments participate in momentum which translate in movements animating the social networks over time. The user finds in these time frames occasions for exchanges where he defines his use of his viewing experience which becomes a moment of expression of a digital identity.